Only bioactive forms of PTH (n-oxPTH and Met18(ox)-PTH) inhibit synthesis of sclerostin - evidence from in vitro and human studies - Li, Mei; Hasan, Ahmed A.; Chu, Chang; Hocher, Johann-Georg; Liu, Yvonne; Zhang, Xiaoli; Chen, Xin; Yard, Benito A.; Krämer, Bernhard; Hocher, Berthold (Pflügers Archiv, 2024)
Sclerostin (SOST) is produced by osteocytes and is known as a negative regulator of bone homeostasis. Parathyroid hormone (PTH) regulates calcium, phosphate as well as vitamin D metabolism, and is a strong inhibitor of SOST synthesis in vitro and in vivo. PTH has two methionine amino acids (positions 8 and 18) which can be oxidized. PTH oxidized at Met18 (Met18(ox)-PTH) continues to be bioactive, whereas PTH oxidized at Met8 (Met8(ox)-PTH) or PTH oxidized at Met8 and Met18 (Met8, Met18(di-ox)-PTH) has minor bioactivity. How non-oxidized PTH (n-oxPTH) and oxidized forms of PTH act on sclerostin synthesis is unknown. The effects of n-oxPTH and oxidized forms of PTH on SOST gene expression were evaluated in UMR106 osteoblast-like cells. Moreover, we analyzed the relationship of SOST with n-oxPTH and all forms of oxPTH in 516 stable kidney transplant recipients using an assay system that can distinguish in clinical samples between n-oxPTH and the sum of all oxidized PTH forms (Met8(ox)-PTH, Met18(ox)-PTH, and Met8, Met18(di-ox)-PTH). We found that both n-oxPTH and Met18(ox)-PTH at doses of 1, 3, 20, and 30 nmol/L significantly inhibit SOST gene expression in vitro, whereas Met8(ox)-PTH and Met8, Met18(di-ox)-PTH only have a weak inhibitory effect on SOST gene expression. In the clinical cohort, multivariate linear regression showed that only n-oxPTH, but not intact PTH (iPTH) nor oxPTH, is independently associated with circulating SOST after adjusting for known confounding factors. In conclusion, only bioactive PTH forms such as n-oxPTH and Met18(ox)-PTH, inhibit SOST synthesis.
Gesehen am 06.08.2024